A kind of anti-corrosion wear-resistant graphite carbon sleeve roll and its manufacturing process

CN122878148APending Publication Date: 2026-10-09SHAANXI WEILIAN HAIGE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611310717.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0002]碳套辊是连续退火炉的关键部件,主要支撑带钢的运行,其表面状态直接影响带钢表面质量,目前各带钢片生产厂家大多采用石墨碳套作为连续退火炉炉底辊,然而,石墨辊虽然具有优良的耐热性、自润滑性和适当的硬度,但其致命的弱点是抗氧化性能差,特别是在920℃以上的高温区使用寿命极短,影响生产的正常进行,生产成本也难以承受,碳套炉底辊在连退炉内高温环境下长期使用容易产生结瘤,使带钢产生亮印、划伤及硌伤等缺陷,在生产过程中,由于碳套辊面结瘤、碳套辊面磨损严重、碳套破裂等原因,对钢带表面质量造成严重影响时,必须及时更换碳套,碳套辊印缺陷是由于炉辊表面结瘤与高温带钢接触,使带钢表面产生具有周期性的凸凹包所致,为此,针对上述描述中提出的问题,本发明提出一种抗腐耐磨石墨碳套辊及其制造工艺

Benefits of technology

[0026]1、本发明通过多元稀土与过渡金属协同改性的磷酸盐浸渍液对碳套进行真空加压浸渍,使改性液充分渗入碳套内部微孔,在气孔内壁形成致密的抗氧化保护膜;再通过两次沉积在碳套表面构建SiC过渡层和SiC/ZrO2复合功能层,形成热膨胀系数梯度过渡的陶瓷涂层,有效隔绝外部氧化气氛,三者协同实现了从基体内部到气孔内壁再到表面外层的全立体防护,有效延缓了石墨基体在高温环境下的氧化进程,减少了碳套辊面因氧化而产生的结瘤现象,从而降低了因辊面结瘤导致带钢产生亮印、划伤及硌伤等缺陷的风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878148A_ABST
    Figure CN122878148A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of low-carbon materials, and particularly relates to a kind of anti-corrosion wear-resistant graphite carbon sleeve roll and manufacturing process thereof, including adding needle coke and pitch into dispersion liquid, adopting die forming to make carbon sleeve roll green body, carrying out baking of carbon sleeve roll green body under nitrogen protection, immersing carbon sleeve after baking in modified impregnation liquid, carrying out high-temperature graphitization treatment of carbon sleeve after impregnation under argon protection, depositing carbon sleeve after graphitization in mixed gas environment, cooling to room temperature to obtain anti-corrosion wear-resistant graphite carbon sleeve roll.The present application carries out vacuum pressurized impregnation of carbon sleeve by phosphate impregnation liquid modified by multiple rare earth and transition metal in cooperation, makes modified liquid fully infiltrate into the internal micropore of carbon sleeve, forms dense oxidation-resistant protective film on the inner wall of air hole;SiC transition layer and SiC / ZrO2 composite functional layer are further constructed on the surface of carbon sleeve by twice deposition, ceramic coating with gradient transition of thermal expansion coefficient is formed, which effectively isolates external oxidation atmosphere.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of low-carbon materials technology, and in particular to a corrosion-resistant and wear-resistant graphite carbon roller and its manufacturing process. Background Technology

[0002] Carbon sleeve rollers are key components of continuous annealing furnaces, primarily supporting the movement of strip steel. Their surface condition directly affects the surface quality of the strip steel. Currently, most strip steel manufacturers use graphite carbon sleeves as the bottom rollers of continuous annealing furnaces. However, although graphite rollers possess excellent heat resistance, self-lubrication, and appropriate hardness, their fatal weakness is poor oxidation resistance, especially in high-temperature zones above 920℃, resulting in extremely short service life, affecting normal production and making production costs unbearable. Long-term use of carbon sleeve bottom rollers in the high-temperature environment of continuous annealing furnaces easily leads to nodule formation, causing defects such as bright marks, scratches, and abrasions on the strip steel. During production, when nodule formation, severe wear, or breakage of the carbon sleeve roller surface seriously affect the surface quality of the steel strip, the carbon sleeve must be replaced promptly. The carbon sleeve roller marks are caused by the contact between nodules on the furnace roller surface and the high-temperature strip steel, resulting in periodic bumps and depressions on the strip steel surface. Therefore, to address the problems described above, this invention proposes a corrosion-resistant and wear-resistant graphite carbon sleeve roller and its manufacturing process. Summary of the Invention

[0003] The purpose of this invention is to provide a corrosion-resistant and wear-resistant graphite carbon roller and its manufacturing process to solve the problems mentioned in the background art.

[0004] To achieve the above objectives, the present invention provides the following technical solution: a manufacturing process for a corrosion-resistant and wear-resistant graphite carbon roller, comprising the following steps:

[0005] S1. Add needle coke and asphalt to the dispersion liquid, mix and stir for 1-2 hours to obtain a mixture. Heat the mixture at 150-200℃ and knead for 30-60 minutes. Then, use molding to form a carbon sleeve roller green body with a pressing pressure of 100-200MPa and a holding time of 5-10 minutes.

[0006] S2. The carbon sleeve roll blank is heated to 1000-1200℃ at a heating rate of 1-5℃ / min under nitrogen protection and held at that temperature for 20-30h for calcination. The calcined carbon sleeve is then impregnated in a modified impregnation solution and pressurized to 0.8-1.2MPa for 2-4h to obtain the impregnated carbon sleeve.

[0007] S3. Cure the impregnated carbon sleeve at 100-150℃ for 2-4 hours, repeat the impregnation-curing process 2-3 times, heat the impregnated carbon sleeve to 2400-2800℃ under argon protection, keep it at that temperature for 10-20 hours for high-temperature graphitization treatment, and place the graphitized carbon sleeve in a mixed gas environment for the first deposition.

[0008] S4. After the first deposition, a second deposition is carried out in a mixed gas system. After the second deposition, the mixture is cooled to room temperature at 2-5℃ / min to obtain corrosion-resistant and wear-resistant graphite carbon rollers.

[0009] The dispersion is prepared through the following steps:

[0010] S11. Add graphite powder to the mixed acid and reflux at 80-120℃ for 12-24 hours. Then dilute, filter, and dialyze to obtain a graphite dispersion.

[0011] S12. Add graphene oxide powder to graphite dispersion and ultrasonically disperse for 30-60 minutes to obtain a mixture. Add multi-walled carbon nanotubes to the mixture and continue ultrasonic dispersion for 1-2 hours.

[0012] S13. Stir at 60-80℃ for 4-6 hours to obtain a dispersion.

[0013] As a preferred embodiment of the present invention, the modified impregnation solution in S2 is prepared by the following steps:

[0014] S21. Mix aluminum dihydrogen phosphate, magnesium dihydrogen phosphate and sodium tripolyphosphate evenly and then add them to deionized water to prepare a mixed solution.

[0015] S22. Under stirring conditions, yttrium nitrate, lanthanum nitrate, cerium nitrate, and zirconium nitrate are added to the mixed solution in sequence.

[0016] S23. Adjust the pH to 2-4 with nitric acid to obtain a modified solution, add polyethylene glycol, and stir at 60-80℃ for 1-2 hours to obtain a modified impregnation solution.

[0017] As a preferred embodiment of the present invention, the mass ratio of needle coke, pitch and dispersion in S1 is (70-90):(10-30):(3-5).

[0018] As a preferred embodiment of the present invention, the mass ratio of the calcined carbon sleeve to the modified impregnation liquid in S2 is 1:(6-8).

[0019] As a preferred embodiment of the present invention, the mixed gas in S3 is composed of methyltrichlorosilane, hydrogen and argon in a volume ratio of 1:(70-90):(290-310), the first deposition temperature is 1000-1200℃, and the deposition time is 2-6h.

[0020] As a preferred embodiment of the present invention, the mixed gas system in S4 is composed of methyltrichlorosilane, hydrogen, argon and zirconium tetrachloride in a volume ratio of 1:(70-80):(250-270):(1-3), the second deposition temperature is 1000-1200℃ and the deposition time is 4-8h.

[0021] As a preferred embodiment of the present invention, the mass ratio of graphite powder to mixed acid in S11 is 1:(30-50), wherein the mixed acid is composed of concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 1:(0.3-0.5).

[0022] As a preferred embodiment of the present invention, the mass ratio of graphene oxide powder to graphite dispersion in S12 is 1:(5-15), and the mass ratio of multi-walled carbon nanotubes to the mixture is 1:(5-15).

[0023] As a preferred embodiment of the present invention, the mass ratio of aluminum dihydrogen phosphate, magnesium dihydrogen phosphate, sodium tripolyphosphate and deionized water in S21 is 1:(0.3-0.5):(0.1-0.3):(2-4); the mass ratio of the mixed solution, yttrium nitrate, lanthanum nitrate, cerium nitrate and zirconium nitrate in S22 is 1:(0.01-0.02):(0.01-0.02):(0.008-0.01):(0.03-0.05); and the mass ratio of the modified solution and polyethylene glycol in S23 is 1:(0.02-0.04).

[0024] As a preferred technical solution of the present invention, a corrosion-resistant and wear-resistant graphite carbon roller is manufactured according to the aforementioned manufacturing process.

[0025] Compared with the prior art, the beneficial effects of the present invention are:

[0026] 1. This invention uses a phosphate impregnation solution modified with a combination of rare earth elements and transition metals to perform vacuum pressure impregnation on a carbon sleeve, allowing the modified solution to fully penetrate the micropores inside the carbon sleeve and form a dense anti-oxidation protective film on the inner wall of the pores. Then, by depositing a SiC transition layer and a SiC / ZrO2 composite functional layer on the surface of the carbon sleeve twice, a ceramic coating with a gradient transition coefficient of thermal expansion is formed, which effectively isolates the external oxidizing atmosphere. The three work together to achieve full three-dimensional protection from the inside of the substrate to the inner wall of the pores and then to the outer surface layer, effectively delaying the oxidation process of the graphite substrate under high temperature environment, reducing the nodulation phenomenon on the surface of the carbon sleeve roller caused by oxidation, thereby reducing the risk of defects such as bright marks, scratches and bruises on the strip steel caused by nodulation on the roller surface.

[0027] 2. This invention employs yttrium nitrate, lanthanum nitrate, cerium nitrate, and zirconium nitrate to synergistically modify the phosphate impregnation solution. Yttrium nitrate improves the wettability of the impregnation solution on the graphite surface in the low-temperature region, ensuring protective effectiveness there. Lanthanum nitrate and cerium nitrate form a dense rare-earth oxide protective layer in the medium-temperature region, filling the protective gap there. Zirconium nitrate forms a thermally stable zirconium silicate phase in the high-temperature region, significantly reducing the oxygen diffusion rate. The synergistic effect of the four modifiers enables the impregnation solution to provide effective protection across a wide temperature range from low to ultra-high temperatures. This effectively solves the technical problem that existing phosphate-impregnated carbon sleeves cannot be used for extended periods above 920°C, while also avoiding the corrosion of the metal roller core by phosphorus-containing substances generated from the decomposition of phosphate at high temperatures. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the preparation process of the corrosion-resistant and wear-resistant graphite carbon roller in this invention;

[0029] Figure 2 This is a schematic diagram of the preparation process of the dispersion in this invention;

[0030] Figure 3 This is a schematic diagram of the preparation process of the modified impregnation solution in this invention. Detailed Implementation

[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Please see Figures 1-3 This invention provides a technical solution for a corrosion-resistant and wear-resistant graphite carbon roller and its manufacturing process:

[0033] Example 1:

[0034] A manufacturing process for a corrosion-resistant and wear-resistant graphite carbon roller includes the following steps:

[0035] I. Preparation of the dispersion:

[0036] S11. Weigh 5g of graphite powder and add 150g of mixed acid (where the mass ratio of concentrated sulfuric acid to concentrated nitric acid is 1:0.3). Reflux at 80℃ for 12h, then dilute, filter, and dialyze to obtain a graphite dispersion.

[0037] S12. Weigh 2g of graphene oxide powder and add it to 10g of graphite dispersion. Disperse the mixture by ultrasonication for 30min to obtain a mixed solution. Then weigh 2g of multi-walled carbon nanotubes and add them to 10g of the mixed solution. Continue to disperse the mixture by ultrasonication for 1h.

[0038] S13. Stir at 60℃ for 4 hours to obtain a dispersion.

[0039] II. Preparation of Modified Impregnation Solution:

[0040] S21. Weigh 10g of aluminum dihydrogen phosphate, 3g of magnesium dihydrogen phosphate, and 1g of sodium tripolyphosphate, add them to 20g of deionized water, mix well, and prepare a mixed solution.

[0041] S22. Under stirring conditions, add 0.2g of yttrium nitrate, 0.2g of lanthanum nitrate, 0.16g of cerium nitrate, and 0.6g of zirconium nitrate to every 20g of mixed solution in sequence.

[0042] S23. Adjust the pH to 2 with nitric acid to obtain a modified solution. Add 0.4g of polyethylene glycol to every 20g of modified solution and stir in a 60℃ water bath for 1h to obtain a modified impregnation solution.

[0043] III. Preparation of Corrosion-Resistant and Wear-Resistant Graphite Carbon Roller:

[0044] S1. Weigh 70g of needle coke and 10g of asphalt, add them to 3g of dispersion liquid, mix and stir for 1 hour to obtain a mixture; heat the mixture at 150℃ and knead for 30 minutes; use molding to form a carbon sleeve roller green body with a pressing pressure of 100MPa and a holding time of 5 minutes.

[0045] S2. The carbon sleeve roll blank is heated to 1000℃ at a heating rate of 1℃ / min under nitrogen protection and held at that temperature for 20h for calcination. Take 5g of the calcined carbon sleeve and impregnate it in 30g of modified impregnation liquid. Pressurize it to 0.8MPa and hold it for 2h to obtain the impregnated carbon sleeve.

[0046] S3. The impregnated carbon sleeve is cured at 100℃ for 2 hours, and the impregnation-curing process is repeated twice. The impregnated carbon sleeve is heated to 2400℃ under argon protection and held at that temperature for 10 hours for high-temperature graphitization treatment. The graphitized carbon sleeve is placed in a mixed gas environment for the first deposition. The flow rate of methyltrichlorosilane in the mixed gas is 10 sccm, the flow rate of hydrogen is 700 sccm, the flow rate of argon is 2900 sccm, the deposition temperature is 1000℃, and the deposition time is 2 hours.

[0047] S4. After the first deposition, a second deposition is carried out in a mixed gas system. The mixed gas has a flow rate of 10 sccm for methyltrichlorosilane, a flow rate of 700 sccm for hydrogen, a flow rate of 2500 sccm for argon, and a flow rate of 10 sccm for zirconium tetrachloride. The deposition temperature is 1000℃ and the deposition time is 4h. After the second deposition, the mixture is cooled to room temperature at a rate of 2℃ / min under a protective atmosphere to obtain corrosion-resistant and wear-resistant graphite carbon rollers.

[0048] Example 2:

[0049] A manufacturing process for a corrosion-resistant and wear-resistant graphite carbon roller includes the following steps:

[0050] I. Preparation of the dispersion:

[0051] S11. Weigh 5g of graphite powder and add 200g of mixed acid (where the mass ratio of concentrated sulfuric acid to concentrated nitric acid is 1:0.4). Reflux at 100℃ for 18h, then dilute, filter, and dialyze to obtain a graphite dispersion.

[0052] S12. Weigh 2g of graphene oxide powder and add it to 20g of graphite dispersion. Disperse the mixture by ultrasonication for 45min to obtain a mixed solution. Then weigh 2g of multi-walled carbon nanotubes and add them to 20g of the mixed solution. Continue to disperse the mixture by ultrasonication for 1.5h.

[0053] S13. Stir at 70℃ for 5 hours to obtain a dispersion.

[0054] II. Preparation of Modified Impregnation Solution:

[0055] S21. Weigh 10g of aluminum dihydrogen phosphate, 4g of magnesium dihydrogen phosphate, and 2g of sodium tripolyphosphate, add them to 30g of deionized water, mix well, and prepare a mixed solution.

[0056] S22. Under stirring conditions, add 0.3g of yttrium nitrate, 0.3g of lanthanum nitrate, 0.18g of cerium nitrate, and 0.8g of zirconium nitrate to every 20g of mixed solution in sequence.

[0057] S23. Adjust the pH to 3 with nitric acid to obtain a modified solution. Add 0.6g of polyethylene glycol to every 20g of modified solution and stir in a 70℃ water bath for 1.5h to obtain a modified impregnation solution.

[0058] III. Preparation of Corrosion-Resistant and Wear-Resistant Graphite Carbon Roller:

[0059] S1. Weigh 80g of needle coke and 20g of asphalt, add them to 4g of dispersion liquid, mix and stir for 1.5h to obtain a mixture; heat the mixture at 180℃ and knead for 45min; use molding to form a carbon sleeve roller green body with a pressing pressure of 150MPa and a holding time of 8min.

[0060] S2. The carbon sleeve roll blank is heated to 1100℃ at a heating rate of 3℃ / min under nitrogen protection and held at that temperature for 25h for calcination. Take 5g of the calcined carbon sleeve and impregnate it in 35g of modified impregnation liquid, pressurize it to 1MPa, and hold it for 3h to obtain the impregnated carbon sleeve.

[0061] S3. The impregnated carbon sleeve is cured at 130℃ for 3 hours, and the impregnation-curing process is repeated twice. The impregnated carbon sleeve is heated to 2600℃ under argon protection and held at that temperature for 15 hours for high-temperature graphitization treatment. The graphitized carbon sleeve is placed in a mixed gas environment for the first deposition. The flow rate of methyltrichlorosilane in the mixed gas is 10 sccm, the flow rate of hydrogen is 800 sccm, the flow rate of argon is 3000 sccm, the deposition temperature is 1100℃, and the deposition time is 4 hours.

[0062] S4. After the first deposition, a second deposition is carried out in a mixed gas system. The mixed gas has a flow rate of 10 sccm for methyltrichlorosilane, a flow rate of 750 sccm for hydrogen, a flow rate of 2600 sccm for argon, and a flow rate of 20 sccm for zirconium tetrachloride. The deposition temperature is 1100℃ and the deposition time is 6h. After the second deposition, the mixture is cooled to room temperature at 3℃ / min under a protective atmosphere to obtain corrosion-resistant and wear-resistant graphite carbon rollers.

[0063] Example 3:

[0064] A manufacturing process for a corrosion-resistant and wear-resistant graphite carbon roller includes the following steps:

[0065] I. Preparation of the dispersion:

[0066] S11. Weigh 5g of graphite powder and add 250g of mixed acid (where the mass ratio of concentrated sulfuric acid to concentrated nitric acid is 1:0.5). Reflux at 120℃ for 24h, then dilute, filter, and dialyze to obtain a graphite dispersion.

[0067] S12. Weigh 2g of graphene oxide powder and add it to 30g of graphite dispersion. Disperse the mixture by ultrasonication for 60min to obtain a mixed solution. Then weigh 2g of multi-walled carbon nanotubes and add them to 20g of the mixed solution. Continue to disperse the mixture by ultrasonication for 2h.

[0068] S13. Stir at 80℃ for 6 hours to obtain a dispersion.

[0069] II. Preparation of Modified Impregnation Solution:

[0070] S21. Weigh 10g of aluminum dihydrogen phosphate, 5g of magnesium dihydrogen phosphate, and 3g of sodium tripolyphosphate, add them to 40g of deionized water, mix well, and prepare a mixed solution.

[0071] S22. Under stirring conditions, add 0.4g of yttrium nitrate, 0.4g of lanthanum nitrate, 0.2g of cerium nitrate, and 1g of zirconium nitrate to every 20g of mixed solution in sequence.

[0072] S23. Adjust the pH to 4 with nitric acid to obtain a modified solution. Add 0.8g of polyethylene glycol to every 20g of modified solution and stir in an 80℃ water bath for 2h to obtain a modified impregnation solution.

[0073] III. Preparation of Corrosion-Resistant and Wear-Resistant Graphite Carbon Roller:

[0074] S1. Weigh 90g of needle coke and 30g of asphalt, add them to 5g of dispersion liquid, mix and stir for 2 hours to obtain a mixture; heat the mixture at 200℃ and knead for 60 minutes; use molding to form a carbon sleeve roller green blank with a pressing pressure of 200MPa and a holding time of 10 minutes.

[0075] S2. The carbon sleeve roll blank is heated to 1200℃ at a heating rate of 5℃ / min under nitrogen protection and held at that temperature for 30h for calcination. Take 5g of the calcined carbon sleeve and impregnate it in 40g of modified impregnation liquid. Pressurize it to 1.2MPa and hold it for 4h to obtain the impregnated carbon sleeve.

[0076] S3. The impregnated carbon sleeve is cured at 150℃ for 4 hours, and the impregnation-curing process is repeated 3 times. The impregnated carbon sleeve is heated to 2800℃ under argon protection and held at that temperature for 20 hours for high-temperature graphitization treatment. The graphitized carbon sleeve is placed in a mixed gas environment for the first deposition. The flow rate of methyltrichlorosilane in the mixed gas is 10 sccm, the flow rate of hydrogen is 900 sccm, the flow rate of argon is 3100 sccm, the deposition temperature is 1200℃, and the deposition time is 6 hours.

[0077] S4. After the first deposition, a second deposition is carried out in a mixed gas system. The mixed gas has a flow rate of 10 sccm for methyltrichlorosilane, a flow rate of 800 sccm for hydrogen, a flow rate of 2700 sccm for argon, and a flow rate of 30 sccm for zirconium tetrachloride. The deposition temperature is 1200℃ and the deposition time is 8h. After the second deposition, the mixture is cooled to room temperature at 5℃ / min under a protective atmosphere to obtain corrosion-resistant and wear-resistant graphite carbon rollers.

[0078] Comparative Example 1:

[0079] Comparative Example 1 differs from Example 1 in that the dispersion is replaced with an equal mass of deionized water, while the remaining steps are exactly the same as in Example 1.

[0080] Comparative Example 2:

[0081] Comparative Example 2 differs from Example 1 in that the modified impregnation solution is replaced with an equal mass of phosphate impregnation solution, while the remaining steps are exactly the same as in Example 1.

[0082] Comparative Example 3:

[0083] Comparative Example 3 differs from Example 1 in that the dispersion was replaced with an equal mass of deionized water, and the modified impregnation solution was replaced with an equal mass of phosphate impregnation solution. The remaining steps were exactly the same as in Example 1.

[0084] Standard samples were cut radially from the corrosion-resistant and wear-resistant graphite carbon rollers prepared in Examples 1-3 and Comparative Examples 1-3. The sample dimensions were processed according to the requirements of each test item, and the following performance tests were performed on the samples.

[0085] I. Density Testing:

[0086] According to GB / T24528-2009 "Determination of Bulk Density of Carbon Materials", the sample was dried at 105-110℃ to constant weight, and the dried mass was measured. The sample was boiled in water for 2 hours to ensure that the water fully penetrated the open pores. After cooling to room temperature, the saturated mass was weighed. The saturated sample was suspended in water, and the suspended mass was weighed. Calculate the bulk density using the following formula:

[0087]

[0088] in, To determine the density of water (g / cm³) at the test temperature. 3 );

[0089] Calculate apparent porosity using the following formula:

[0090]

[0091] II. High-Temperature Antioxidant Performance Testing:

[0092] Referring to ASTM C1179-21 "Standard Test Method for Oxidation Mass Loss of Man-made Carbon and Graphite Materials in Air" and ASTM D7542-21 "Standard Test Method for Oxidation of Carbon and Graphite in Air in Kinetics", the sample was processed into a cylinder with dimensions of φ20mm × 20mm. The sample surface was cleaned with anhydrous ethanol, dried at 105-110℃ to constant weight, and the initial mass was measured using an analytical balance. The sample was placed in a high-temperature tube furnace and heated to 800℃, 920℃, 1050℃, and 1200℃ respectively at a heating rate of 5℃ / min in air atmosphere. Oxidation was carried out at each temperature for 10 hours. After oxidation, the sample was cooled to room temperature in the furnace, and its mass after oxidation was measured. Calculate the oxidation weight loss rate using the following formula:

[0093]

[0094] III. Thermal shock resistance test:

[0095] Referring to the sample processing requirements in GB / T3074.4-2016 "Method for Determination of Thermal Expansion Coefficient of Graphite Electrodes", and combining the industry-standard water quenching method, the thermal shock resistance performance test was carried out. The sample was processed into a cylinder with a size of φ20mm×20mm. The sample was placed in a high-temperature furnace and held at 1000℃ for 15min. The sample was then quickly removed and immersed in cold water at 25±5℃ to complete one thermal shock cycle. The sample was then removed and dried at 105-110℃. The above thermal shock cycle was repeated until visible cracks or peeling appeared on the sample surface. The number of thermal shock cycles was recorded.

[0096] IV. Abrasion resistance test:

[0097] Referring to GB / T12444-2006 "Test Methods for Wear of Metallic Materials - Sliding Wear Test of Test Rings and Blocks" and industry-standard methods, the specimen was machined into a cylinder with dimensions of φ20mm×20mm, and the end face was ground smooth. A pin-disc friction and wear testing machine was used for testing. A GCr15 bearing steel disc (hardness HRC60-62) was applied at room temperature and 600℃, with a load of 50N, and the specimen slid at a speed of 0.5m / s for 1000m. The specimen mass was weighed before and after the test, and the wear amount was calculated. The wear rate was calculated using the following formula:

[0098]

[0099] in, The wear mass loss is (g). For load (N). The sliding distance (m) is shown in Table 1.

[0100] Table 1: Performance Test Table of Corrosion-Resistant and Wear-Resistant Graphite Carbon Roller Samples

[0101]

[0102] As can be seen from the data in Table 1, Comparative Example 1, lacking the nano-reinforcing network of graphene oxide and multi-walled carbon nanotubes within the matrix, exhibits significantly lower wear resistance than the other examples. This demonstrates that the present invention effectively improves the self-lubricating properties and wear resistance of the carbon roller by introducing graphene oxide and multi-walled carbon nanotubes into the matrix. Meanwhile, Comparative Example 2, lacking the multi-element rare earth / zirconium-modified phosphate protective layer, is more prone to accelerated wear due to oxidation under high-temperature wear conditions, further verifying the synergistic effect between impregnation solution modification and nano-reinforcement.

[0103] In summary, this invention achieves comprehensive protection from the interior of the matrix to the inner wall of the pores and then to the outer surface layer through a three-dimensional protection strategy integrating matrix nano-reinforcement, internal pore protection, and surface coating isolation. The corrosion-resistant and wear-resistant graphite carbon roller prepared by this invention is significantly superior to the comparative examples of existing technologies in terms of density, high-temperature oxidation resistance, thermal shock resistance, and wear resistance. Among them, Example 2 has slightly better overall performance than Examples 1 and 3 due to its moderate process parameters. This fully demonstrates the scientific nature and advancement of the technical solution of this invention, and has important practical application value for solving the technical problems of poor oxidation resistance and short service life of graphite carbon rollers in the high-temperature section of continuous annealing furnaces.

[0104] The above are merely specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent substitutions, or modifications made based on the present invention to solve essentially the same technical problems and achieve essentially the same technical effects are all covered within the protection scope of the present invention.

Claims

1. A manufacturing process for a corrosion-resistant and wear-resistant graphite carbon roller, characterized in that, Includes the following steps: S1. Add needle coke and asphalt to the dispersion liquid, mix and stir for 1-2 hours to obtain a mixture, heat the mixture at 150-200℃ and knead for 30-60 minutes, and use molding to form a carbon sleeve roller green body with a pressing pressure of 100-200MPa and a holding time of 5-10 minutes. S2. The carbon sleeve roll blank is heated to 1000-1200℃ at a heating rate of 1-5℃ / min under nitrogen protection and held at the temperature for 20-30h for calcination. The calcined carbon sleeve is then impregnated in a modified impregnation solution, pressurized to 0.8-1.2MPa, and held for 2-4h to obtain the impregnated carbon sleeve. S3. The impregnated carbon sleeve is cured at 100-150℃ for 2-4 hours. The impregnation-curing process is repeated 2-3 times. The impregnated carbon sleeve is heated to 2400-2800℃ under argon protection and kept at that temperature for 10-20 hours for high-temperature graphitization treatment. The graphitized carbon sleeve is placed in a mixed gas environment for the first deposition. S4. After the first deposition is completed, a second deposition is carried out in a mixed gas system. After the second deposition is completed, the temperature is cooled to room temperature at 2-5℃ / min to obtain corrosion-resistant and wear-resistant graphite carbon roller. The dispersion is prepared through the following steps: S11. Add graphite powder to the mixed acid and reflux at 80-120℃ for 12-24 hours. Then dilute, filter, and dialyze to obtain a graphite dispersion. S12. Add graphene oxide powder to graphite dispersion and ultrasonically disperse for 30-60 minutes to obtain a mixture. Add multi-walled carbon nanotubes to the mixture and continue ultrasonic dispersion for 1-2 hours. S13. Stir at 60-80℃ for 4-6 hours to obtain a dispersion.

2. The manufacturing process of a corrosion-resistant and wear-resistant graphite carbon roller according to claim 1, characterized in that: The modified impregnation solution in S2 is prepared through the following steps: S21. Mix aluminum dihydrogen phosphate, magnesium dihydrogen phosphate and sodium tripolyphosphate evenly and then add them to deionized water to prepare a mixed solution. S22. Under stirring conditions, yttrium nitrate, lanthanum nitrate, cerium nitrate, and zirconium nitrate are added sequentially to the mixed solution; S23. Adjust the pH to 2-4 with nitric acid to obtain a modified solution, add polyethylene glycol, and stir at 60-80℃ for 1-2 hours to obtain a modified impregnation solution.

3. The manufacturing process of a corrosion-resistant and wear-resistant graphite carbon roller according to claim 1, characterized in that: The mass ratio of needle coke, pitch and dispersion in S1 is (70-90):(10-30):(3-5).

4. The manufacturing process of a corrosion-resistant and wear-resistant graphite carbon roller according to claim 1, characterized in that: The mass ratio of the calcined carbon sleeve to the modified impregnation liquid in S2 is 1:(6-8).

5. The manufacturing process of a corrosion-resistant and wear-resistant graphite carbon roller according to claim 1, characterized in that: The mixed gas in S3 is composed of methyltrichlorosilane, hydrogen, and argon in a volume ratio of 1:(70-90):(290-310). The first deposition temperature is 1000-1200℃ and the deposition time is 2-6h.

6. The manufacturing process of a corrosion-resistant and wear-resistant graphite carbon roller according to claim 1, characterized in that: The mixed gas system in S4 is composed of methyltrichlorosilane, hydrogen, argon, and zirconium tetrachloride in a volume ratio of 1:(70-80):(250-270):(1-3). The second deposition temperature is 1000-1200℃ and the deposition time is 4-8h.

7. The manufacturing process of a corrosion-resistant and wear-resistant graphite carbon roller according to claim 1, characterized in that: The mass ratio of graphite powder to mixed acid in S11 is 1:(30-50), wherein the mixed acid is composed of concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 1:(0.3-0.5).

8. The manufacturing process of a corrosion-resistant and wear-resistant graphite carbon roller according to claim 1, characterized in that: The mass ratio of graphene oxide powder to graphite dispersion in S12 is 1:(5-15), and the mass ratio of multi-walled carbon nanotubes to the mixture is 1:(5-15).

9. The manufacturing process of a corrosion-resistant and wear-resistant graphite carbon roller according to claim 2, characterized in that: In S21, the mass ratio of aluminum dihydrogen phosphate, magnesium dihydrogen phosphate, sodium tripolyphosphate, and deionized water is 1:(0.3-0.5):(0.1-0.3):(2-4). In S22, the mass ratio of the mixed solution, yttrium nitrate, lanthanum nitrate, cerium nitrate, and zirconium nitrate is 1:(0.01-0.02):(0.01-0.02):(0.008-0.01):(0.03-0.05). In S23, the mass ratio of the modified solution to polyethylene glycol is 1:(0.02-0.04).

10. A corrosion-resistant and wear-resistant graphite carbon roller, characterized in that, It is manufactured using the manufacturing process according to any one of claims 1-9.